Culture and politics in South Asia
1 online resource (xxvi, 318 pages)
Keywords: "This volume looks at the politics of communication and culture in contemporary South Asia. It explores languages, signs and symbols reflective of current mythologies that underpin instances of performance in present-day India and its neighbouring countries. From gender performances and stage depictions to protest movements, folk songs to cinematic reconstructions and elections to war-torn regions, the chapters in the book bring the multiple voices embedded within the grand theatre of popular performance and the cultural landscape of the region to the fore.Breaking new ground, this work will prove useful to students and researchers in sociology and social anthropology, art and performance studies, political studies and international relations, communication and media studies and culture studies."--Provided by publisher.